Risk assessment of Portuguese population to multiple mycotoxins: the human biomonitoring approach. (13th November 2019) - Martins, C; Vidal, A; De Saeger, S; Nunes, C; Torres, D; Goios, A; Lopes, C; Assunção, R; Alvito, P; De Boevre, M
Abstract: : Mycotoxins constitute a relevant group of food contaminants with several associated health outcomes such as estrogenic, immunotoxic, nephrotoxic and teratogenic effects. Although scarce data are available in Portugal, human biomonitoring studies have been globally developed to assess the exposure to mycotoxins at individual level. The present study concerned the analysis of mycotoxins in 24h urine and first-morning urine paired samples from 94 participants enrolled within the scope of the National Food, Nutrition, and Physical Activity Survey of the Portuguese General Population (2015-2016). Following a salt-assisted matrix extraction, urine samples were analyzed by liquid chromatography-mass spectrometry for the simultaneous determination of 37 urinary mycotoxins' biomarkers and data obtained used to estimate the probable daily intake as well as the risk characterization applying the Hazard Quotient approach. Results revealed the exposure of Portuguese population to zearalenone, deoxynivalenol, ochratoxin A, alternariol, citrinin and fumonisin B1 through the quantification in 24h urine and first-morning urine paired samples. Risk characterization data revealed a potential concern to some reported mycotoxins since the reference intake values were exceeded by some of the considered participants. Alternariol was identified for the first time in urine samples from a European country; however, risk characterization was not performed due to lack of reference intake value. The present study contributed with reliable and evidence-based results, and confirmed that mycotoxins represent a burden and are part of the human exposome of the Portuguese population. Further studies are needed to shed a light on the determinants of exposure in order to contribute for the promotion of public health measures to reduce the mycotoxins' exposure in Portugal. Key messages: Portuguese population is exposed to mycotoxins, chemical food contaminants that may be harmful (carcinogenic, immunotoxic, mutagenic, teratogenic, hepatotoxic) for human health. Human biomonitoring studies provide realistic data on internal exposure at individual level, allowing a more accurate knowledge of the determinants of exposure to these contaminants.